A study on the effect of sludge concentrations on the efficiency of wastewater treatment by SBR technology - Thu, Van Thi; Hanh, Vo Thi My; Uan, Do Khac (Petrovietnam Journal, 2014)
In this study, a lab-scale SBR system was used to treat wastewater. In particular, the effect of sludge concentrations (MLSS) on the system treatment effi ciency was examined. The infl uent wastewater parameters were varied largely, i.e. COD concentration of 425 - 836mg/l; TN concentration of 61.3 - 82.7mg/l, and TP concentration of 6,6 - 25,3mg/l. The observed results showed that at the MLSS level of 1,000mg/l, the treatment efficiencies of COD, TN, and TP were about 72.2%, 76.2%, and 57.4%, respectively. It was interesting that when MLSS was increased to 2,000mg/l, the treatment efficiencies of COD, TN, and TP were increased up to 83.0%, 81.1%, and 60.4%, respectively. However, when MLSS was continuously increased to 3,000mg/l, the treatment efficiencies of COD and TN were decreased down to 68.1% and 58.6%, respectively. Whereas, the TP removal efficiency was increased up to 68.4%. The SVI was relatively stable and was in the range of 63 - 72mL/g MLSS. It meant that the sludge was settled well. Based on the fi ndings, the MLSS concentration of 2,000mg/l would be a proper condition for operating the SBR system to treat domestic wastewater.